MDA4SOA+d: A new model driven architecture to supporting decision making in SOA - Boumahdi, Fatima; Oqaibi, Hadi; Chalal, Rachid; Hentabli, Hamza; Madani, Amina (Journal of King Saud University. Computer and information sciences, 2023)
The utilization of Model-Driven Architecture (MDA) in Service Oriented Architecture (SOA) is a concept that has been introduced previously and published research is available on this subject. However, the main research s’ubject of this paper, fusing MDA and decision aspects as autonomous building blocks that form a full SOA, is a ground-breaking concept. This paper proposes an integrated model-driven solution method that will help develop service-oriented architectures while being aware of the need for decisions. Furthermore, our goal is to explore the standard models at every defined level; this is one of our primary reasons for utilizing the Service oriented architecture Modeling Language (SoaML) and the Decisional Model Notation (DMN) standard in designing several services. We also present a service taxonomy that defines the new set of concepts needed to model three dimensions. The proposed approach is called MDA4SOA+d (Model Driven Architecture for SOA with Decision Aspect), and it offers, among other benefits, a more comprehensive understanding of the entire system and the platform-independent development. It also enhances the reusability of the designs and simplifies the system’s evolution, thus enhancing productivity. The proposed approach will be illustrated with a case study for an IT Equipment Bid Evaluation process.